Parâmetros físicos e químicos da água, balanço de massa e a ictiofauna de quatro microbacias hidrográficas do Sistema Paraíba do Sul e sua correlação com a geomorfologia regional - Lourenço, Jeferson de Moraes Rocha Medeiros Freitas [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In this research, were studied 4 micro watersheds that, together, consist of an area of approximately 500 km² distributed in the east sierra of Mantiqueira and Vale do Paraíba in the state of São Paulo. The highest sources of these micro watersheds are located in the summit section of the Mantiqueira at about 2000 meters of altitude where they form streams, which subsequently descend abruptly the Mantiqueira escarpment and then run across the plain of the Vale do Paraíba until they achieve the Paraíba river at much lower altitudes, which, in general, are around 550 meters high. From these micro watersheds were collected environmental data relating to the physical and chemical parameters of water, vegetation and regional geomorphology through fieldwork and the use of geotechnology. The physical and chemical data were used to evaluate the annual dynamic and mass balance of these elements for each of the 4 micro watersheds, once fluviometric and rainfall data were collected. The analysis of the physical and chemical micro watersheds data showed that the rates of physical and chemical weathering are higher in the upper fluvial channels of the micro watersheds and in the rainy season of the year. Their rainwater and river water had concentrations within the normal range for most chemical elements measured except for the pH of precipitation, which remained acid throughout the year, and the Na concentrations in the rainwater showed noticeable higher values than those measured in other studies. In this research, the Ichthyofauna was also studied by evaluating whether there is a correlation between the regional geomorphology characteristics of the studied micro watersheds regarding the richness, abundance, Shannon diversity, equitability and similarity of the fish fauna. The results showed that all regional geomorphological variables used have an important role in the regional structure of fish communities; however, the slope of the main...

Nesta pesquisa foram estudadas 4 microbacias hidrográficas que perfazem uma área de aproximadamente 500 km², localizadas na serra da Mantiqueira oriental e Vale do Paraíba, no estado de São Paulo. As microbacias têm suas nascentes mais altas localizadas no setor de cimeira da Mantiqueira, a quase 2000 metros de altitude, onde formam riachos que, posteriormente, descem a escarpa da Mantiqueira de forma abrupta e, em seguida, correm pela planície do Vale do Paraíba, até atingir o rio Paraíba em altitudes muito inferiores que, no geral, estão ao redor dos 550 metros. Nestas microbacias foram coletados dados ambientais relativos aos parâmetros físicos e químicos da água, cobertura vegetal e geomorfologia regional, através do emprego de trabalhos de campo e do uso de geotecnologias . Os dados físicos e químicos foram utilizados para avaliar a dinâmica anual e balanço de massa destes elementos para cada uma das 4 microbacias, uma vez que foram coletados dados fluviométricos e pluviométricos. A análise dos dados físicos e químicos das microbacias demonstrou que as taxas de intemperismo físico e químico são mais acentuadas no alto curso das microbacias e no período mais chuvoso do ano; suas águas pluviais e fluviais apresentaram concentrações dentro dos padrões normais da maioria dos elementos químicos mensurados, com exceção para o pH das precipitações que permaneceu ácido durante todo o ano e as concentrações de Na das águas pluviais que apresentaram valores sensivelmente superiores aos verificados em outros estudos. Nesta pesquisa também foi estudada a ictiofauna, avaliando se existe correlação entre as características geomorfológicas regionais das microbacias estudadas com a riqueza, abundância, diversidade Shannon, equitabilidade e similaridade da fauna de peixes. Os resultados demonstraram que todas as variáveis geomorfológicas regionais utilizadas têm um relevante papel na estruturação das...
Keywords: Geomorphology; Geomorfologia; Bacias hidrograficas; Ictiofauna; Quimica da agua; Mantiqueira, Serra da